2003
DOI: 10.1021/ja0380502
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Fluorescence Probes of Protein Kinase Activity

Abstract: We introduce a versatile fluorescent peptide reporter of protein kinase activity. The probe can be modified to target a desired kinase by changing the kinase recognition motif in the peptide sequence. The reporter motif contains the Sox amino acid, which generates a fluorescence signal when bound to Mg2+ present in the reaction mixture. The phosphorylated peptide exhibits a much greater affinity for Mg2+ than its unphosphorylated analogue and, thus, a greater fluorescence intensity. Product formation during ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(158 citation statements)
references
References 11 publications
1
150
0
1
Order By: Relevance
“…These FlAAs can be incorporated into kinase recognition peptide motifs and report on serine/threonine or tyrosine phosphorylation events via enhanced fluorescence emission in the presence of Mg 2+ . 62 The emission signal (~485 nm) relies on the formation of a chelate between the 8-hydroxyquinoline and the installed phosphoryl group, which shows a 15-20-fold greater affinity for Mg 2+ relative to the nonphosphorylated hydroxyl group. Peptide probes containing the Sox/C-Sox amino acid for a variety of kinases have been synthesized and implemented for kinase measurements with recombinant enzymes and in unfractionated cell lysates, yielding fluorescence enhancements of ~2-12-fold.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
See 1 more Smart Citation
“…These FlAAs can be incorporated into kinase recognition peptide motifs and report on serine/threonine or tyrosine phosphorylation events via enhanced fluorescence emission in the presence of Mg 2+ . 62 The emission signal (~485 nm) relies on the formation of a chelate between the 8-hydroxyquinoline and the installed phosphoryl group, which shows a 15-20-fold greater affinity for Mg 2+ relative to the nonphosphorylated hydroxyl group. Peptide probes containing the Sox/C-Sox amino acid for a variety of kinases have been synthesized and implemented for kinase measurements with recombinant enzymes and in unfractionated cell lysates, yielding fluorescence enhancements of ~2-12-fold.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…Peptide probes containing the Sox/C-Sox amino acid for a variety of kinases have been synthesized and implemented for kinase measurements with recombinant enzymes and in unfractionated cell lysates, yielding fluorescence enhancements of ~2-12-fold. [62][63][64] It was also found that substitution of the sulfonamide moiety on C-Sox by various substituted triazole groups (installed via click chemistry) gave rise to a multitude of novel Mg 2+ -chelating hydroxyquinoline FlAAs with fluorescence emission maxima that are shifted up to 40 nm. 65 These new click derivatives were incorporated into peptide substrates for study of the MK2 kinase and shown to be as efficiently turned over as C-Sox-containing peptides.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…36,37 Human lung cancer cells (PC9) were encapsulated in droplets along with a specific tyrosine kinase substrate with and without a specific modulator (epidermal growth factor, EGF). The binding of EGF to its cell surface receptor, EGFR, triggers receptor dimerization, allowing tyrosine in the cytoplasmic portion of the receptor monomer to be trans-phosphorylated by its partner receptor, thus, aiding in signal propagation.…”
Section: -1058/2014/8(3)/034104/9mentioning
confidence: 99%
“…In the presence of a phosphorylated peptide, binding of the second Zn(II) to the free dpa site is facilitated, and as a result, the PET quenching is suppressed and the fluorescence intensity recovers. Recently, Lawrence et al 28 and Imperiali et al 29 have reported some peptide-based fluorescent probes for protein kinase activity that possess the sensing mechanism analogous to that of our chemosensors. In these sensing systems, a phosphate group attached to the substrate peptide by a kinase reaction intra-molecularly induces Ca 2þ or Mg 2þ binding to the fluorophore that is adjacently connected to the phosphorylation residues, which consequently results in the fluorescence enhancement.…”
Section: Artificial Chemosensors For Single Phosphate Groups On Protementioning
confidence: 99%